2022
DOI: 10.1021/acsami.1c21096
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystalline Elastomers Based on Click Chemistry

Abstract: Liquid crystalline elastomers (LCEs) have emerged as an important class of functional materials that are suitable for a wide range of applications, such as sensors, actuators, and soft robotics. The unique properties of LCEs originate from the combination between liquid crystal and elastomeric network. The control of macroscopic liquid crystalline orientation and network structure is crucial to realizing the useful functionalities of LCEs. A variety of chemistries have been developed to fabricate LCEs, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 154 publications
0
22
0
Order By: Relevance
“…The synthesis of the matrix network of thiol-acrylate MC-LCE was via a sol-gel processed two-step Michael addition and polymerization reaction coupled with a stretching process between the two steps (TAMAP). [71][72][73][74] As illustrated in Fig. 1(a), the precursor reactants included the monomers of mesogen (RM257), flexible network backbone (PEG250), chain extender (EDDET), and crosslinker (PETMP).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the matrix network of thiol-acrylate MC-LCE was via a sol-gel processed two-step Michael addition and polymerization reaction coupled with a stretching process between the two steps (TAMAP). [71][72][73][74] As illustrated in Fig. 1(a), the precursor reactants included the monomers of mesogen (RM257), flexible network backbone (PEG250), chain extender (EDDET), and crosslinker (PETMP).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used three laser organic dyes, whose absorption bands were in the visible spectral region but mutually separated, to fabricate dye-doped LCE materials. Main-chain LCE (MC-LCE) matrices based on thiol-acrylate systems [71][72][73][74] were selected as the host materials. Our previous work indicated that LCEs doped with any one of these three visible absorber dyes could be effectively actuated by quasi-daylight irradiation for the reason that the emission spectrum of quasi-daylight covered their absorption bands while these visible absorber dyes have a strong light-absorbing ability and photothermal conversion effect.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years, “click” chemistry has become the most widely used reaction for the interconversion of two or more functional groups, such as alkyl, alkenyl, alkyne, phenyl, hydroxyl, carbonyl, ester, amino, or thiol, among other moieties [18e,40] . This chemistry encompasses the facile synthesis of new compounds with extraordinary properties by reactions characterized as more efficient, high yielding, orthogonal, regioselective, kinetically fast, thermodynamically favorable, and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…introduced for the first time the two‐stage thiol‐acrylate Michael addition and photopolymerization (TAMAP) reaction to prepare and program main‐chain LCEs with permanently aligned monodomains [41] . From then on, different type of click reactions has been implemented for LCE synthesis, [18e] such as aza‐Michael, thiol‐epoxy, and so forth, which will be discussed throughout the review.…”
Section: Introductionmentioning
confidence: 99%
“…Responsive polymers with large and reversible mechanical responses have facilitated access to functional materials capable of performing tasks ranging from muscle-like actuators to small-scale walking robots. , One of the most promising classes of stimuli-responsive materials are liquid-crystal elastomers (LCEs) and liquid-crystal networks (LCNs). , Although they differ in chemical composition, cross-linking, and thermomechanical properties they both retain the unique liquid-crystalline properties that Pierre-Gilles de Gennes predicted would exhibit a sizable stimuli response upon disruption of order within the polymer network . The order–disorder transition of liquid-crystal (LC) molecules incorporated into a network drives a conformational change of the polymer chains, which is the underlying mechanism often responsible for the reversible deformation .…”
mentioning
confidence: 99%